Re-envisioning Theodore: Theodore of Mopsuestia's biblical exegesis in his "Catechetical homilies" - Puchkova, Sofia ca. 20./21. Jh. (Vigiliae Christianae, 2025)
Re-envisioning Theodore is the first comprehensive study of Theodore of Mopsuestia's biblical interpretation in his Catechetical Homilies . It challenges the common yet reductionist view of Theodore’s exegetical approach as “historical,” offering a balanced portrayal of this exegete. Theodore is not a slave of his interpretative methodology, and he may omit the exposition of the historical setting of the Bible and introduce elements not present in the biblical narrative. Re-envisioning Theodore also reveals Theodore’s previously little known exegetical ties with Pro-Nicenes and, through them, with Origen. For the first time, this book shows that his exegesis incorporates Greco-Syrian liturgical imagery